'In the hospital all is taken care of': a practice‐theoretical approach to understand patients' medication use. Issue 1 (18th August 2019) - Reichenpfader, Ursula; Wickström, Anette; Abrandt Dahlgren, Madeleine; Carlfjord, Siw
Abstract: Drawing from case examples of medication review implementation in three hospital settings in Sweden, this article examines patients' medication use. Based on a practice theory approach and utilising data from interviews with patients and participant observation, we reconstruct three practices of everyday medication use centring on accepting, challenging or appropriating medication orders. This article argues that patients' medication practices are embedded in wider practice arrangements that afford different modes of agency. Reconceptualising patients' medication use from a practice‐based perspective revealed the meaning‐making, order‐producing and identity‐forming features of these practices. Also, we illustrated how different modes of agency were achieved in patients' medication practices, suggesting a fluidity of both the meanings attached to and the identities related to medication use. Our findings have practical implications as these practices of medication use can be transformed when altering the arrangements they are embedded in, thus going beyond the clinical encounter.